Evaluation of Effects of Radiofrequency Ablation of Ex vivo Liver Using the 1-Fr Wire Electrode. Issue 2 (February 2018) - Rustagi, Tarun; Gleeson, Ferga C.; Abu Dayyeh, Barham K.; Topazian, Mark D.; Levy, Michael J.
Abstract : Background and Study Aims: Percutaneous and intraoperative radiofrequency ablation (RFA) has become a valued tool in the management of primary and secondary hepatic lesions. A recent FDA-approved endoscopic ultrasound (EUS)-guided RFA probe now offers promise to help manage such lesions. However, there are no data to determine the ideal power setting and duration of ablation needed to effectively treat hepatic masses. The aim of the study was to evaluate the macroscopic zone of hepatic injury for EUS-RFA using a variety of settings within a fresh porcine hepatic specimen. Methods: RFA was performed using the Habib EUS-RFA needle (EMcision Ltd, London, UK) which is a 1-Fr wire (0.33 mm, 0.013 inch) with a working length of 190 cm. A step by step approach to deliver radiofrequency energy at 5, 10, 15, 20, and 50 W of power and 10, 30, 60, 90, 120, and 300 seconds, respectively, was followed. Macroscopic and microscopic findings of the ablation zone were evaluated at each setting. Results: The maximal zone (diameter, 8.2±0.14 mm; length, 20.85±0.21 mm) of coagulative necrosis was achieved using an ablation power of 10 W for duration of 90 seconds. Notably, increased power settings resulted in an unexpected and diminished effect on tissue destruction. Conclusions: Our findings support the use of 10 W power for 90 seconds for maximum ablation in the liver. Our data also provide initial guidance and alternate settings to be considered when performing EUS-RFA to adjust the ablation power and duration to match the lesion size, shape, and risk of injury to adjacent structures.